Pemahaman Tentang Keselamatan dalam Yohanes 3:16 Serta Anugerah, Iman, Keselamatan dan Salib Versi Hki - Yossi Pratiwi Pardosi; Ebenezer Nainggolan; Dewi Sinamo; Siska Hutagalun; Liyus Waruwu (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This type of research is qualitative research and aims to provide an understanding of salvation in John 3:16 and God's promise of salvation to every believer. Salvation comes from the Greek word 'sozo' which means to save, liberate, preserve, preserve and heal. When related to humans, salvation is healing from death or maintaining life. Where the first humans created by God were Adam and Eve in a holy state without sin. Humans were created by God to be given the freedom to choose what is good and what is bad. But humans choose the wrong path so that humans' relationship with God is severed and spiritually they experience death. For this reason, salvation is needed by humans who have experienced spiritual death. And salvation is received by everyone because of grace and it is God's action to make humans receive eternal life again. This research also examines the eternal nature of salvation for believers, as well as how God's promise of salvation brings hope and certainty to His people. In conclusion, John 3:16 offers a view of salvation as God's eternal gift, given to every believer in Jesus Christ and is the basis for Christian faith in God's redemptive love.